Comparison of Microclimate Characteristics Based on Air Temperature in Vegetated Areas and Residential Areas in Palopo - Ari Affandy Mahyuddin; Rahmat Hidayat Dongka; Fajar Ramadhan (Universitas Andi Djemma Palopo, 2026)
The city of Palopo, a developing city on the eastern coast of South Sulawesi, is experiencing the intensive conversion of green spaces into residential in tandem with ongoing urbanization, a process that has direct implications for urban microclimate dynamics but has not yet been extensively studied through direct field measurements in this region. This study aims to analyze and compare microclimate characteristics based on air temperature parameters between vegetated areas and residential areas in Palopo City. Measurements were taken at ten sampling points, five in vegetated areas and five in residential areas, during three time periods (morning, noon, and afternoon) using a DHT11 digital temperature sensor. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and an independent samples t-test. The results showed that the average air temperature in vegetated areas was 29.46 °C, significantly lower than that in residential areas, which reached 30.40 °C, with an average difference of 0.94 °C (t = 6.78; p < 0.001; df = 8). The largest temperature difference was recorded during the day (1.38 °C), reflecting the contrast in heat absorption and release patterns between the vegetation canopy and the hard surface materials of residential areas. The daily temperature amplitude in vegetated areas (1.66 °C) is narrower than that in residential areas (2.68 °C), confirming the role of vegetation as a thermal buffer that stabilizes microclimate conditions. These findings provide an empirical basis for understanding the characteristics of tropical urban microclimates and for more measured planning of green open space distribution in the city of Palopo.